Development and Validation of the Post-Bereavement Growth Scale (PBGS): A Turkish Sample Study - Kaya, Muhammet Enes; Kumova, Filiz (Routledge, 2025)
The loss of a close one is commonly construed as a painful experience and addressed predominantly in terms of its pathological aspects. However bereaved individuals may also experience psychological growth following loss. The present study examined the experience of loss from a multidimensional perspective, developing the Post‑Bereavement Growth Scale (PBGS). Participants, 335 adults aged 18–65 who experienced the death of a close one between 3 and 24 months prior, answered the questions online. Additionally, as part of the validity analyses, they also completed measures of personal development and meaninglessness-emptiness. For reliability analyses, 30 participants completed the PBGS twice, 4 weeks apart. The psychometric evaluation of the PBGS yielded a 26‑item, five‑factor structure. Subscales were Functioning, Personal Resources, Relational Coping, Making Sense of Life, and Adaptation. The findings indicated that the PBGS possesses satisfactory validity and reliability.